2015
DOI: 10.1007/s11128-015-1091-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing user privacy in SARG04-based private database query protocols

Abstract: The well-known SARG04 protocol can be used in a private query application to generate an oblivious key. By usage of the key, the user can retrieve one out of N items from a database without revealing which one he/she is interested in. However, the existing SARG04-based private query protocols are vulnerable to the attacks of faked data from the database since in its canonical form, the SARG04 protocol lacks means for one party to defend attacks from the other. While such attacks can cause significant loss of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…The quantum theory has been applied in many filed including information theory [38], decision making system [49,50], social and information networks [46,51]. Busemeyer et al [5,33] proposed a Quantum Dynamical model based on a quantum version of a classical dynamical Markov model, which takes the process of making decisions into account of time evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum theory has been applied in many filed including information theory [38], decision making system [49,50], social and information networks [46,51]. Busemeyer et al [5,33] proposed a Quantum Dynamical model based on a quantum version of a classical dynamical Markov model, which takes the process of making decisions into account of time evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Yang et al [10] introduced the concept of semi-quantumness [11,12] into QPQ to design the first semi-quantum private query (SQPQ) protocol. Unfortunately, Yu et al [13] pointed out that the user privacy can be invaded unconsciously in the protocol of Ref. [10], and suggested an improved protocol to overcome this loophole.…”
Section: Introductionmentioning
confidence: 99%
“…[10], and suggested an improved protocol to overcome this loophole. However, Yu et al's improved protocol [13] is not semi-quantum. In 2019, Pei et al [14] put forward a practical QPQ protocol of blocks based on the two-dimensional QKD system; Chang et al [15] suggested a practical two-way QKD-based QPQ protocol with better performance in user privacy; Ma et al [16] proposed a QPQ protocol based on stable error correcting code in the case of noise; Xiao et al [17] constructed an efficient QPQ protocol based on Oracle and Grover iteration.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain the phenomenon and predict the interference effect, some models have been proposed like the quantum Belief-action entanglement(BAE) model proposed by Zheng Wang and Busemeyer [2], an exemplar model account of feature inference proposed by Nosofsky R.M [3] and so on. Quantum information has a wide application, like user security [4,5], quantum communication [6,7] and so on. Quantum theory has been widely applied in the field of cognition and decision [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%